Microstructure and superelastic properties of free forged Ti–Ni shape-memory alloy - Bahador, Abdollah; Hamzah, Esah; Kondoh, Katsuyoshi; Asma Abubakar, Tuty; Yusof, Farazila; Umeda, Junko; Saud, Safaa N.; Ibrahim, Mustafa K. (Elsevier, 2018)
Elemental titanium (Ti) and nickel (Ni) powders were consolidated by spark plasma sintering (SPS) to fabricate Ti–51%Ni (mole fraction) shape-memory alloys (SMAs). The objective of this study is to enhance the superelasticity of SPS produced Ti–Ni alloy using free forging as a secondary process. Products from two processes (with and without free forging) were compared in terms of microstructure, transformation temperature and superelasticity. The results showed that, free forging effectively improved the tensile and shape-memory properties. Ductility increased from 6.8% to 9.2% after forging. The maximum strain during superelasticity increased from 5% to 7.5% and the strain recovery rate increased from 72% to 92%. The microstructure of produced Ti–51%Ni SMA consists of the cubic austenite (B2) matrix, monoclinic martensite (B19′), secondary phases (Ti3Ni4, Ti2Ni and TiNi3) and oxides (Ti4Ni2O and Ti3O5). There was a shift towards higher temperatures in the martensitic transformation of free forged specimen (aged at 500 °C) due to the decrease in Ni content of B2 matrix. This is related to the presence of Ti3Ni4 precipitates, which were observed using transmission electron microscope (TEM). In conclusion, free forging could improve superelasticity and mechanical properties of Ti–51%Ni SMA.